2014
DOI: 10.1037/a0037481
|View full text |Cite
|
Sign up to set email alerts
|

Daily reports of intimate partner verbal aggression by self and partner: Short-term consequences and implications for measurement.

Abstract: Objective Agreement within couples regarding the occurrence of aggression is surprisingly low. Survey research often collapses across partners’ reports to create a pooled estimate of aggression in the relationship. This method ignores possible differences in partners’ perceptions of the event, potentially weakening researchers’ ability to detect consequences of aggression. The current study examines both partners’ reports of verbal aggression to determine whether aggression reported by only one partner influen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
26
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 30 publications
(28 citation statements)
references
References 41 publications
2
26
0
Order By: Relevance
“…Consistent with the theme that IPA is viewed as unacceptable, participants expressed distress that they were aggressive, that they wished to aggress, or that there was aggression in their relationships. These findings are consistent with a recent daily diary study showing that self-reported episodes of partner physical aggression, whether involving victimization or perpetration, had negative effects on subsequent mood and relationship functioning (Derrick et al, 2014). …”
Section: Discussionsupporting
confidence: 91%
“…Consistent with the theme that IPA is viewed as unacceptable, participants expressed distress that they were aggressive, that they wished to aggress, or that there was aggression in their relationships. These findings are consistent with a recent daily diary study showing that self-reported episodes of partner physical aggression, whether involving victimization or perpetration, had negative effects on subsequent mood and relationship functioning (Derrick et al, 2014). …”
Section: Discussionsupporting
confidence: 91%
“…That is, we considered the effects of each person's own marijuana use on his or her perpetration (a and a′ or Actor paths) as well as the effects of each person's use on partner's aggression (p and p′ paths). A recent study using the APIM found independent effects of actor and partner alcohol use on both perpetration and victimization over 56 days of daily reports in a community sample of regular drinkers (Testa & Derrick, 2014).…”
Section: Marijuana Effects Within Intimate Relationshipsmentioning
confidence: 96%
“…Furthermore, research shows that men and women experience comparable amounts of depression, anxiety, and posttraumatic stress at low levels of psychological victimization, and women experience even more severe outcomes as the frequency of violence increases (Harned, 2001). Derrick, Testa, and Leonard (2014) found that both perpetrators and victims reported worse moods and lower relationship functioning after a psychologically abusive interaction, suggesting that this kind of abuse has negative effects for both couple members and the relationship itself. Thus, it is significant to establish a clear understanding of the perceptions of psychological abuse, as its impact is prevalent and can result in severe consequences.…”
Section: Psychological Abuse Is Pervasive and Harmfulmentioning
confidence: 99%